عقد المرابحة بين الشريعة والقانون - عبد الحق, باسو (جامعة الوادي - University eloued, 2022)
عقد المرابحة أحد الصيغ التي تتعامل بها البنوك اليوم في عصرنا الحاضر ،وهو أكثر العقود قبولا بين المتعاملين مع البنوك لما له من إمتيازات تبرزه عن باقي الصيغ لا سيما قلت المخاطر مقارنة بالعقود الأخرى . وهذا العقد كما تجريه البنوك يتم إبرامه تماشيا مع خطوت محددة ،كي ينشأ آثاره صحيحة فهو يمر بمرحلتين أساسيتين ،أولاهما تكون تمهيدية والأخرى ينعقد فيها البيع مرابحة ،مع مراعات الضوابط الشرعية والقانونية التي تنظم هذا العقد ،كي يتفادى الأطراف الوقوع في المخاطر والتجاوزات التي من شأنها أن تبطل هذا العقد Murabaha contract is one of the formulate use it by Banks today in this present era.its famous and popular contract acceptance between clients and Banks , that's what included a lot of benefits compare with other formulas , special less of dangerous and risque if its compare with other contract. This kind of contract utilized by banks related to new steps for establish and prove right effect, that's because move with two stage, first is preparatory and the second is make it the sale by Murabaha contract , with take into consideration the law and legitimagy reglemention to organize this contract That's for make all the parts and persons avoid the risque that's can caused to invalidate the contract
مذكرة ماستر
Keywords: البنوك ، عقد المرابحة ، الآمر بالشراء ، العميل ، المورد ، المخاطر; Banks , Murabaha contract , Purchaser , Clients , Supplier , risque .